Utilization of Instagram: Efforts to Introduce Publishing Study Program and Publishing Works to the Community - Diah Amelia; Nurul Akmalia (2022)
This article discusses the selection of Instagram as a promotional medium in introducing the Creative Media State Polytechnic Publishing study program and publishing works. Information such as photos or videos of work products, pictures of learning activities, and other activities added to the Instagram account. This information can be seen by followers and can get a response or input directly. The study used qualitative research methods with a descriptive approach. The theory used is New Media and Internet theory, Social Media theory, and Marketing Communication theory. The study results explain that the use of Instagram significantly facilitates the spread of messages quickly and reaches more people. The content on the Instagram account @prodi.penerbitan.polimedia follows the institution's image but still has to be packaged in an attractive style and design and has new value.